(untitled) (Bangladesh Pharmaceutical Journal, 2013)
Activated carbon prepared from sawdust is endeavored as adsorbent for the removal of reactive dye, namely Remazol Red (RR) from aqueous media. The adsorption of RR has been studied onto activated sawdust at various particle size, adsorbent dose, temperature and pH values. The adsorptions of the above mentioned dye were designed for the Langmuir and Freundlich Isotherms. Pseudo first and second order kinetic models were used to calculate the amount adsorbed at equilibrium (qe). The calculated values of qe for pseudo-second order equation were found to be in good agreement with those of experimental values. The monolayer capacity (qm) for treated sawdust (8.00 mg g1) is greater than commercial charcoal (0.074 mg g1). It is established that treated sawdust has been used as a better adsorbent for the removal of RR as compared to commercial charcoal. This process may eventually be used to get industrial waste free purified water. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14501 Bangladesh Pharmaceutical Journal 16(1): 93-98, 2013